Amino-functionalized liquid crystal dye, coating type polaroid and preparation method of coating type polaroid

By using a combination of amino-functionalized liquid crystal dye and acrylic and other materials, coated polarizers are prepared by shear coating and ultraviolet curing, which solves the problems of insufficient viscosity, hardness and weather resistance of coated polarizers in the prior art, and achieves efficient polarization performance and good physical characteristics, which are suitable for flexible display screens.

CN119662277APending Publication Date: 2025-03-21GUANGDONG LIYUAN NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411841535.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing coated polarizers have poor viscosity, hardness and weather resistance, making it difficult to meet the needs of flexible display screens.

Method used

The amino-functionalized liquid crystal dye was mixed with acrylic acid, photoinitiator and crosslinking agent, coated on the substrate by shear coating, and ultraviolet irradiation was used to cure to obtain a coated polarizer.

Benefits of technology

It improves the maximum polarization efficiency of the coated polarizer, enhances its adhesion strength, surface hardness, weather resistance and thermal stability to various substrates, and is suitable for low-cost flexible displays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119662277A_ABST
    Figure CN119662277A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polaroid preparation, and discloses an amino-functionalized liquid crystal dye, a coating type polaroid and a preparation method thereof.The preparation method of the coating type polaroid comprises the steps that the amino-functionalized liquid crystal dye is dissolved in acrylic acid, then a photoinitiator and a cross-linking agent are added, and the coating type polaroid is prepared. The liquid crystal dye is one or more of N, N-[bis-(diethylaminoethyl)] perylene-3, 4, 9, 10-tetracarboxylic acid diimine, N, N-[bis (N-(2-aminoethyl) piperidine)] perylene-3, 4, 9, 10-tetracarboxylic acid diimine, N, N-[bis-(dimethylaminoethyl)] perylene-3, 4, 9, 10-tetracarboxylic acid diimine and N, N-[bis-(diethylaminopropyl)] perylene-3, 4, 9, 10-tetracarboxylic acid diimine; a substrate is coated with the liquid crystal coating through a shear coating method, then ultraviolet irradiation is carried out, and the coating type polaroid is prepared. The polaroid prepared by the preparation method disclosed by the invention shows excellent optical and physical characteristics, and shows excellent weather resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polarizers, and particularly relates to an amino-functionalized liquid crystal dye, a coated polarizer and a preparation method thereof. Background Art

[0002] Polarizers with light penetration / shielding functions can be used in display devices such as liquid crystals and liquid crystal displays (LCDs) with light switching functions. They can also be used in lenses with polarization functions, such as polarized glasses used in sunglasses, 3D TVs, etc.

[0003] Conventional polarizers are generally made by dyeing a film with iodine or a dichroic dye or making the film contain dichroic substances such as iodine or a dichroic dye. The film is a film of polyvinyl alcohol PVA or its derivatives that has been stretched and oriented, or a polyolefin film that is generated by dehydrating a polyvinyl chloride film or a polyvinyl alcohol film to generate a polyolefin and orient it. Among them, the iodine-based polarizer using iodine has excellent polarizing properties, and the dye-based polarizer using a dichroic dye has excellent moisture resistance and heat resistance compared to the iodine-based polarizer. At present, the most widely used stretched polarizer is the H-type polarizer, which is made of a stretched polyvinyl alcohol film impregnated with iodine. This polarizer has the advantages of broadband absorption, high dichroism and relatively low cost. However, due to the fact that iodine (I 3- and I 5- ) has low heat resistance and moisture resistance, and the mechanical strength of the PVA film itself is also weak. Therefore, the PVA film must be additionally protected by triacetyl cellulose film (TAC). Moreover, this polarizer is usually about 100-200μm thick, which cannot meet the requirements of thin and ultra-thin display applications.

[0004] At present, display devices are rapidly developing in the direction of curved surfaces and flexibility. In 2019, flexible display technology has begun to be applied in specific ways, especially in foldable OLED smartphones, becoming a new direction of technical research and application; for example, to achieve a breakthrough in flexible OLED display technology, it not only faces the problem of high-frequency folding, but also needs to maintain its original state after folding, which puts higher requirements on the softness and windability of polarizers, and the thinning of polarizers has become a development trend. In order to meet the requirements of curved surfaces and flexibility, the OLED polarizers that match them will also develop in the direction of thinness and flexibility. How to achieve thinning of OLED polarizers is the current key technical problem.

[0005] Foreign countries started research on coated polarizers early, and a large number of such research results have been published to replace traditional stretched polarizers. Among them, the use of dichroic coated polarizers based on lyotropic chromonic liquid crystals (LLC) system is one way. The LLC system is a representative of one-dimensional molecular self-assembly, and the phase change of its liquid crystal phase material changes with the concentration of liquid crystal molecules in the solvent. Single molecules have a plate-like shape, and once the concentration exceeds a certain critical concentration, they will aggregate into rod-like aggregates to form a smectic phase structure. The absorption peaks of these LLC molecules are selected or regulated in the visible region. They generally show anisotropic absorption after being subjected to shear force, so they can be used to prepare coated polarizers.

[0006] Remizow, S et al. [Remizow S, Krivoshchepov A, Nazarov V, et al. Rheology of the lyotropic liquid crystalline material for thin film polarizers] used lyotropic liquid crystals and dyes and obtained a coated polarizer by shearing. The rheological properties of the lyotropic liquid crystals as a new type of Optiva thin film polarizer coating material at different temperatures and concentrations were studied. This type of water-based lyotropic liquid crystal is formed by supramolecular aggregates of modified dichroic dyes. However, since the dichroic dye itself is water-soluble, the weather resistance of the coating formed by it is poor, which is specifically manifested in the decrease in polarization degree of the polarizer after wet and hot aging, and even the complete disappearance of polarization performance.

[0007] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0008] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide an amino-functionalized liquid crystal dye, a coated polarizer and a preparation method thereof, aiming to solve the problems of poor viscosity, hardness and weather resistance of the existing coated polarizers.

[0009] The technical solution of the present invention is as follows:

[0010] An amino-functionalized liquid crystal dye, wherein the liquid crystal dye is one or more of N,N-[bis-(diethylaminoethyl)]perylene-3,4,9,10-tetracarboxylic acid diimide, N,N-[bis(N-(2-aminoethyl)piperidine)]perylene-3,4,9,10-tetracarboxylic acid diimide, N,N-[bis-(dimethylaminoethyl)]perylene-3,4,9,10-tetracarboxylic acid diimide and N,N-[bis-(diethylaminopropyl)]perylene-3,4,9,10-tetracarboxylic acid diimide, and the corresponding chemical formula is:

[0011]

[0012] A method for preparing a coated polarizer, comprising the steps of:

[0013] The amino-functionalized liquid crystal dye of the present invention is dissolved in acrylic acid, and then a photoinitiator and a cross-linking agent are added and mixed to prepare a liquid crystal coating;

[0014] The liquid crystal coating is coated on a substrate by a shear coating method, and then ultraviolet irradiation is performed to obtain a coated polarizer.

[0015] The method for preparing the coated polarizer, wherein the cross-linking agent is one or more of EO-TMPTA, EO-TMTA and PETA.

[0016] The method for preparing the coated polarizer, wherein the photoinitiator is TPO or photoinitiator-184.

[0017] The method for preparing the coated polarizer comprises the following steps: in the step of dissolving the amino-functionalized liquid crystal dye in acrylic acid, the mass ratio of the liquid crystal dye to the acrylic acid is 1:2-3.

[0018] The method for preparing the coated polarizer, wherein the usage ratio of the photoinitiator to acrylic acid is 1-2:100.

[0019] The method for preparing the coated polarizer, wherein the usage ratio of the crosslinking agent to acrylic acid is 2-10:10.

[0020] The method for preparing the coated polarizer, wherein the substrate is a glass substrate or a plastic substrate.

[0021] A coated polarizer is prepared by the method for preparing the coated polarizer of the present invention.

[0022] Beneficial effects: The present invention provides a novel method for preparing a coatable polarizer, wherein one or more of a class of amino-functionalized liquid crystal dyes, such as N,N'-[bis(diethylaminoethyl)]perylene-3,4,9,10-tetracarboxylic acid diimide, N,N-[bis(N-(2-aminoethyl)piperidine)]perylene-3,4,9,10-tetracarboxylic acid diimide, N,N-[bis-(dimethylaminoethyl)]perylene-3,4,9,10-tetracarboxylic acid diimide, and N,N-[bis-(diethylaminopropyl)]perylene-3,4,9,10-tetracarboxylic acid diimide, are dissolved in an acrylic acid solution containing a photoinitiator and a crosslinking agent to prepare a liquid crystal coating, which is then coated by a shear coating method and subsequently irradiated with ultraviolet rays to obtain a coatable polarizer. The coating process of this organic-based solution has excellent performance, especially on plastic substrates. The measured maximum polarization efficiency exceeds 98%. The resulting thin-film polarizer shows excellent optical and physical properties, such as good adhesion strength to various substrates, excellent surface hardness, good weather resistance and good thermal stability, which is crucial for low-cost flexible displays. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The present invention is a flow chart of a method for preparing a coated polarizer.

[0024] Figure 2 This is a cross-polarized microscope image of the lyotropic liquid crystal prepared in Example 2-1.

[0025] Figure 3 This is a cross-polarized microscope image of the lyotropic liquid crystal prepared in Example 2-1 after shear coating.

[0026] Figure 4 This is a cross-polarized microscope image of the lyotropic liquid crystal prepared in Example 2-2.

[0027] Figure 5 This is a cross-polarized microscope image of the lyotropic liquid crystal prepared in Example 2-2 after shear coating. DETAILED DESCRIPTION

[0028] The present invention provides an amino-functionalized liquid crystal dye, a coated polarizer and a preparation method thereof. To make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0029] The terms "first", "second", "third", "fourth", etc. (if any) in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments described herein can be implemented in an order other than that illustrated or described herein. In addition, the terms "including" or "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0030] The present invention provides an amino-functionalized liquid crystal dye, wherein the liquid crystal dye is one or more of N,N'-[bis(diethylaminoethyl)]perylene-3,4,9,10-tetracarboxylic acid diimine, N,N-[bis(N-(2-aminoethyl)piperidine)]perylene-3,4,9,10-tetracarboxylic acid diimine, N,N-[bis-(dimethylaminoethyl)]perylene-3,4,9,10-tetracarboxylic acid diimine, and N,N-[bis-(diethylaminopropyl)]perylene-3,4,9,10-tetracarboxylic acid diimine, and the corresponding chemical formula is:

[0031]

[0032] Based on the amino-functionalized liquid crystal dye, the present invention also provides a method for preparing a coated polarizer, such as Figure 1 As shown, it includes the steps of:

[0033] S10, dissolving the amino-functionalized liquid crystal dye of the present invention in acrylic acid, and then adding a photoinitiator and a cross-linking agent, and mixing to obtain a liquid crystal coating;

[0034] S20, coating the liquid crystal coating on the substrate by a shear coating method, and then irradiating the substrate with ultraviolet light to obtain a coated polarizer.

[0035] The coating process performance of the organic-based solution provided by the present invention is excellent, especially on plastic substrates. The maximum polarization efficiency of the coated polarizer is measured to be over 98%, and the resulting thin-film polarizer exhibits excellent optical and physical properties, such as good adhesion strength to various substrates, excellent surface hardness, good solvent tolerance and good thermal stability, which are crucial for low-cost flexible display screens.

[0036] In some embodiments, the crosslinking agent is one or more of EO-TMPTA, EO-TMTA and PETA, but is not limited thereto. In this embodiment, EO-TMPTA, full name ethoxylated trimethylolpropane triacrylate, is a trimethylolpropane triacrylate (TMPTA) modified by ethoxylation. TMPTA itself is a small molecule crosslinking agent with three acryloyloxymethyl groups, which can undergo free radical polymerization with other monomers to form a highly crosslinked polymer network. Ethoxylation modification may change its physical properties such as solubility and viscosity, making it suitable for the application occasions of this embodiment; EO-TMTA is a trimethylolpropane trimethacrylate modified by ethoxylation, which has similar properties and applications as EO-TMPTA, namely, as a crosslinking agent for photocurable materials; the PETA, the full name of which is pentaerythritol triacrylate, is a crosslinking agent widely used in the fields of chemistry and materials. It contains a side hydroxyl group, has low volatility, and cures quickly, and is mainly used for free radical polymerization; PETA has the main characteristics of high crosslinking density, fast curing, good flexibility, low volatility, scratch resistance, fire resistance and chemical resistance, and is very suitable for this embodiment to be highly crosslinked with acrylic monomers.

[0037] In some embodiments, the photoinitiator is TPO or photoinitiator-184, but is not limited thereto. In this embodiment, the chemical name of TPO is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, which is a highly efficient free radical photoinitiator; the chemical name of photoinitiator-184 is 1-hydroxycyclohexyl phenyl ketone; after absorbing the energy of ultraviolet rays, both can transition from the ground state to the excited state, thereby generating active species such as free radicals or cations. These active species can initiate the polymerization reaction of acrylic monomers or prepolymers, and are the starting point of the photocuring process; the selection and use of the photoinitiator directly affect the curing speed and efficiency. Efficient photoinitiators can initiate a large number of polymerization reactions in a relatively short period of time, thereby achieving rapid curing and improving production efficiency.

[0038] In some embodiments, in the step of dissolving the amino-functionalized liquid crystal dye in acrylic acid, the mass ratio of the liquid crystal dye to acrylic acid is 1:2-3. Specifically, in this embodiment, since the tertiary amine groups on the liquid crystal dye molecules can form ammonium salts with acrylic acid, the π-π interactions of the conjugated polyaromatic structures in the molecules self-assemble to form a liquid crystal phase. When the mass ratio of the liquid crystal dye to acrylic acid in the mixed solution is less than 1:3, the liquid crystal phase is difficult to form and the transmittance is too high due to the low dye content; when the mass ratio of the liquid crystal dye to acrylic acid in the mixed solution is greater than 1:2, the dissolution of the dye is limited, solids are easily precipitated, and the coating and film-forming properties are poor.

[0039] Furthermore, the mass ratio of liquid crystal dye to acrylic acid will also affect the crosslinking density after curing. The crosslinking density is an important indicator for measuring the degree of internal crosslinking of the material, which directly affects the strength, hardness and wear resistance of the film; as a functional component, the liquid crystal dye has a direct impact on the optical properties of the coating, and changes in the content of the liquid crystal dye may cause changes in the optical properties of the coating, such as light absorption and light transmittance; the mass ratio of the liquid crystal dye to acrylic acid will also affect the adhesion between the coating and the substrate. An appropriate amount of liquid crystal dye can improve the adhesion, but too much or too little may lead to a decrease in adhesion. Based on the above considerations, this embodiment preferably has a mass ratio of the liquid crystal dye to acrylic acid of 1:2-3. Under this ratio, it can also ensure that the prepared coated polarizer has better strength, hardness, wear resistance and light transmittance, and the formed liquid crystal coating has a strong adhesion to the substrate.

[0040] In some embodiments, the ratio of the photoinitiator to the acrylic acid is 1-2:100, but is not limited thereto.

[0041] In some embodiments, the ratio of the cross-linking agent to acrylic acid is 2-10:10, but is not limited thereto.

[0042] In some embodiments, the substrate is a glass substrate or a plastic substrate, but is not limited thereto. Preferably, the substrate is a plastic substrate.

[0043] In some embodiments, a coated polarizer is further provided, wherein the coated polarizer is prepared using the method for preparing the coated polarizer of the present invention.

[0044] The present invention will be further explained below by means of specific embodiments:

[0045] Example 1-1

[0046] A preparation method of an amino-functionalized liquid crystal dye (PDI-1) comprises the following steps:

[0047] 5 g (12.7 mmol) of 3,4,9,10-perylenetetracarboxylic dianhydride and 30 ml of N,N-diethylethylenediamine were mixed and refluxed for 26 h. After cooling, the solid mixture obtained by the reaction was filtered, washed with methanol and ethyl acetate respectively, and dried in a vacuum oven for 24 h to obtain N,N-[bis-(diethylaminoethyl)]perylene-3,4,9,10-tetracarboxylic acid diimide (PDI-1), whose chemical formula is: Yield: 98%.

[0048] Example 1-2

[0049] A preparation method of an amino-functionalized liquid crystal dye (PDI-2) comprises the following steps:

[0050] 5 g (12.7 mmol) of 3,4,9,10-perylenetetracarboxylic dianhydride and 30 g of N-(2-aminoethyl)piperidine were dissolved in 150 ml of DMF, mixed and reacted at 150° C. for 48 h, and the solid mixture obtained by the reaction was filtered after cooling, washed three times with methanol and ethyl acetate respectively, and dried in a vacuum oven for 24 h to obtain N,N-[bis(N-(2-aminoethyl)piperidine)]perylene-3,4,9,10-tetracarboxylic acid diimide (PDI-2), whose chemical formula is: Yield: 86%.

[0051] Examples 1-3

[0052] A preparation method of an amino-functionalized liquid crystal dye (PDI-3) comprises the following steps:

[0053] 5 g (12.7 mmol) of 3,4,9,10-perylenetetracarboxylic dianhydride and 30 ml of N,N-dimethylethylenediamine were mixed and refluxed for 26 h. After cooling, the solid mixture obtained by the reaction was filtered, washed with methanol and ethyl acetate respectively, and dried in a vacuum oven for 24 h to obtain N,N-[bis-(dimethylaminoethyl)]perylene-3,4,9,10-tetracarboxylic acid diimide (PDI-3), whose chemical structure is as follows: Yield: 92%.

[0054] Examples 1-4

[0055] A preparation method of an amino-functionalized liquid crystal dye (PDI-4) comprises the following steps:

[0056] 5 g (12.7 mmol) of 3,4,9,10-perylenetetracarboxylic dianhydride and 30 ml of N,N-diethylpropylenediamine were mixed and refluxed for 26 h. After cooling, the solid mixture obtained by the reaction was filtered, washed with methanol and ethyl acetate respectively, and dried in a vacuum oven for 24 h to obtain N,N-[bis-(diethylaminopropyl)]perylene-3,4,9,10-tetracarboxylic acid diimide (PDI-4), whose chemical formula is: Yield: 78%.

[0057] Example 2-1

[0058] A method for preparing a coated polarizer comprises the following steps:

[0059] 10 g of PDI-1 was heated and dissolved in 30 g of acrylic acid (in a brown bottle, protected from light); then, 0.3 g of photoinitiator TPO (1 wt% relative to the weight of acrylic acid) and 12 g of pentaerythritol triacrylate PETA (40 wt% relative to the weight of acrylic acid) were added to the solution, and ultrasonic treatment was used at a temperature not higher than 40° C. to make them uniformly mixed; then, the obtained composition was coated on a glass substrate or a plastic substrate by shearing, and then irradiated with ultraviolet light (curing energy 500 mJ / cm 2 ), to obtain a coated polarizer.

[0060] Example 2-2

[0061] A method for preparing a coated polarizer comprises the following steps:

[0062] 10 g of PDI-2 was completely dissolved in 30 g of acrylic acid (in a brown bottle, protected from light). Then, 0.3 g of photoinitiator TPO (1 wt% relative to the weight of acrylic acid) and 6 g of ethoxylated trimethylolpropane triacrylate EO-TMTA (20 wt% relative to the weight of acrylic acid) were added to the solution, and ultrasonic treatment was used at a temperature not higher than 40°C to make them uniformly mixed. The resulting composition was then coated on a glass substrate or a plastic substrate by shearing, and then irradiated with ultraviolet light (curing energy 500 mJ / cm 2 ), to obtain a coated polarizer.

[0063] Example 2-3

[0064] A method for preparing a coated polarizer comprises the following steps:

[0065] 10 g of PDI-3 was completely dissolved in 30 g of acrylic acid (in a brown bottle, protected from light). Then, 0.6 g of TPO (2 wt% relative to the weight of acrylic acid), 6 g of PETA (20 wt% relative to the weight of acrylic acid), and 6 g of EO-TMPTA (20 wt% relative to the weight of acrylic acid) were added to the solution, and ultrasonic treatment was used at a temperature not higher than 40°C to make them uniformly mixed. The resulting composition was then coated on a glass substrate or a plastic substrate by shearing, and then irradiated with ultraviolet light (curing energy 1000 mJ / cm 2 ), to obtain a coated polarizer.

[0066] Embodiment 2-4

[0067] A method for preparing a coated polarizer comprises the following steps:

[0068] 10 g of PDI-4 was completely dissolved in 30 g of acrylic acid (in a brown bottle, protected from light). Then, 0.3 g of TPO (1 wt% relative to the weight of acrylic acid) and 12 g of PETA (40 wt% relative to the weight of acrylic acid) were added to the solution and uniformly mixed using ultrasonic treatment at a temperature not higher than 40°C. The resulting composition was then coated on a glass substrate or a plastic substrate by shearing and then irradiated with ultraviolet light (curing energy 1000 mJ / cm 2 ), to obtain a coated polarizer.

[0069] Embodiment 2-5

[0070] A method for preparing a coated polarizer comprises the following steps:

[0071] 10 g of PDI-1 was completely dissolved in 30 g of acrylic acid (in a brown bottle, protected from light). Then, 0.3 g of TPO (1 wt% relative to the weight of acrylic acid) and 12 g of PETA (40 wt% relative to the weight of acrylic acid) were added to the solution and uniformly mixed using ultrasonic treatment at a temperature not higher than 40°C. The resulting composition was then coated on a glass substrate or a plastic substrate by shearing and then irradiated with ultraviolet light (curing energy 1000 mJ / cm 2 ), to obtain a coated polarizer.

[0072] Embodiment 2-6

[0073] A method for preparing a coated polarizer comprises the following steps:

[0074] 10 g of PDI-1 was completely dissolved in 20 g of acrylic acid (in a brown bottle, protected from light). Then, 0.3 g of TPO (1.5 wt% relative to the weight of acrylic acid) and 20 g of PETA (100 wt% relative to the weight of acrylic acid) were added to the solution and uniformly mixed using ultrasonic treatment at a temperature not higher than 40°C. The resulting composition was then coated on a glass substrate or a plastic substrate by shearing and then irradiated with ultraviolet light (curing energy 1000 mJ / cm 2 ), to obtain a coated polarizer.

[0075] Embodiment 2-7

[0076] A method for preparing a coated polarizer comprises the following steps:

[0077] 4 g of PDI-1 and 6 g of PDI-2 were completely dissolved in 20 g of acrylic acid (in a brown bottle, protected from light). Then, 0.3 g of TPO (1.5 wt% relative to the weight of acrylic acid), 10 g of PETA (50 wt% relative to the weight of acrylic acid) and 10 g of EO-TMPTA (50 wt% relative to the weight of acrylic acid) were added to the solution and uniformly mixed using ultrasonic treatment at a temperature not higher than 40°C. The resulting composition was then coated on a glass substrate or a plastic substrate by shearing and then irradiated with ultraviolet light (curing energy 1000 mJ / cm 2 ), to obtain a coated polarizer.

[0078] Embodiment 2-8

[0079] A method for preparing a coated polarizer comprises the following steps:

[0080] 5 g of PDI-1 and 5 g of PDI-2 were completely dissolved in 30 g of acrylic acid (in a brown bottle, protected from light). Then, 0.3 g of photoinitiator-184 (1 wt% relative to the weight of acrylic acid) and 10 g of EO-TMPTA (33.3 wt% relative to the weight of acrylic acid) were added to the solution, and ultrasonic treatment was used at a temperature not higher than 40°C to make them uniformly mixed. The resulting composition was then coated on a glass substrate or a plastic substrate by shearing, and then irradiated with ultraviolet light (curing energy 1000 mJ / cm 2 ), to obtain a coated polarizer.

[0081] Comparative Example 2-1

[0082] A method for preparing a coated polarizer comprises the following steps:

[0083] 10 g of PDI-1 was completely dissolved in 30 g of acrylic acid (in a brown bottle, protected from light). Then, 0.3 g of TPO (1 wt% relative to the weight of acrylic acid) was added to the solution and mixed uniformly using ultrasonic treatment at a temperature not higher than 40°C. The resulting composition was then coated on a glass substrate or a plastic substrate by shearing and then irradiated with ultraviolet light (curing energy 500 mJ / cm 2 ), to obtain a coated polarizer.

[0084] Comparative Example 2-2

[0085] A method for preparing a coated polarizer comprises the following steps:

[0086] 10 g of PDI-1 was completely dissolved in 30 g of 0.1 mol / L hydrochloric acid (in a brown bottle, protected from light), 5 g of polyvinyl alcohol powder (Mw=2000) was added thereto and mixed evenly using ultrasonic treatment at a temperature not higher than 40°C. After cooling to room temperature, the obtained product was coated on a glass substrate or a plastic substrate by shearing, and then heated and dried (temperature 40-60°C) to obtain a coated polarizer.

[0087] Comparative Examples 2-3

[0088] A method for preparing a coated polarizer comprises the following steps:

[0089] 10g of Sunset Yellow (CAS No.: 2783-94-0) was completely dissolved in 30g of acrylic acid aqueous solution (wherein the acrylic acid mass dispersion was 70%, in a brown bottle, protected from light). Then, 0.3g of TPO (1wt% relative to the weight of acrylic acid) was added to the solution, and ultrasonic treatment was used at a temperature not higher than 40°C to make it uniformly mixed. The resulting composition was then coated on a glass substrate or a plastic substrate by shearing, and then irradiated with ultraviolet light (curing energy 1000mJ / cm 2 ), to obtain a coated polarizer.

[0090] Comparative Examples 2-4

[0091] 10g of Sunset Yellow (CAS No.: 2783-94-0) was completely dissolved in 30g of acrylic acid aqueous solution (wherein the acrylic acid mass dispersion was 70%, in a brown bottle, protected from light). Then, 0.3g of TPO (1wt% relative to the weight of acrylic acid) and 12g of PETA (40wt% relative to the weight of acrylic acid) were added to the solution, and ultrasonic treatment was used at a temperature not higher than 40°C to make them uniformly mixed. The resulting composition was then coated on a glass substrate or a plastic substrate by shearing, and then irradiated with ultraviolet light (curing energy 1000mJ / cm 2 ), to obtain a coated polarizer.

[0092] Test Example 1

[0093] The polarization efficiency of the coated polarizers prepared in Examples 2-1 to 2-8 and Comparative Examples 2-1 to 2-3 was measured by a polarizing microscope (POM) and a spectrophotometer, and the physical properties of the films were evaluated by pencil hardness and tape adhesion tests; the change in polarization degree under different temperatures and temperature and humidity conditions was measured to evaluate the weather resistance of such coated polarizers, wherein a polarization degree with a change rate of less than 5% is excellent, a polarization degree change rate between 5-10% is good, a polarization degree change rate between 10-20% is medium, and a polarization degree change rate of more than 20% is poor; the measured results are shown in Table 1.

[0094] Table 2 Performance test results of coated polarizer

[0095]

[0096]

[0097] From the results in Table 1, it can be seen that the weather resistance and hardness of the coated polarizer prepared in the embodiment of the present application are significantly better than those in the comparative example. This is because, on the one hand, the PDI dye synthesized in the embodiment itself has good water resistance (resistance to moisture and heat), and on the other hand, the tertiary amine group on the PDI dye molecule synthesized in the embodiment can form an ammonium salt with non-aqueous acrylic acid, and at the same time, the π-π interaction of the conjugated polyaromatic structure in the molecule self-assembles to form a liquid crystal phase. Within a certain range, as the proportion of acrylic acid monomers increases, after curing and cross-linking, the water resistance and hardness of the formed coating can be improved.

[0098] Test Example 2

[0099] The lyotropic liquid crystal (i.e., liquid crystal coating) prepared in Example 2-1 and Example 2-2 was observed under a cross-polarized light microscope before and after coating. The results are as follows: Figure 2-Figure 5 As shown. Figure 2 This is a cross-polarized microscope image of the lyotropic liquid crystal prepared in Example 2-1, which shows a liquid crystal state; Figure 3 This is a cross-polarized microscope image of the lyotropic liquid crystal prepared in Example 2-1 after shear coating, from which it can be seen that the liquid crystal is arranged in an orderly manner and presents a dark state; Figure 4 is a cross-polarized microscope image of the lyotropic liquid crystal prepared in Example 2-2, which exhibits a liquid crystal state; Figure 5 This is a cross-polarized microscope image of the lyotropic liquid crystal prepared in Example 2-2 after shear coating, from which it can be seen that the liquid crystal is arranged in an orderly manner and presents a dark state. This shows that within a certain concentration range, the synthesized PDI dye can form a nematic liquid crystal, and this nematic liquid crystal can be uniformly oriented in the shear direction after shear coating, so that it presents a dark state on the cross-polarized microscope; at the same time, it is found through spectrophotometer measurement that the formed coating has a high degree of polarization.

[0100] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. An amino-functionalized liquid crystal dye, characterized in that: The liquid crystal dye is one or more of N,N-[bis-(diethylaminoethyl)]perylene-3,4,9,10-tetracarboxylic acid diimide, N,N-[bis(N-(2-aminoethyl)piperidine)]perylene-3,4,9,10-tetracarboxylic acid diimide, N,N-[bis-(dimethylaminoethyl)]perylene-3,4,9,10-tetracarboxylic acid diimide and N,N-[bis-(diethylaminopropyl)]perylene-3,4,9,10-tetracarboxylic acid diimide, and the corresponding chemical formula is:

2. A method for preparing a coated polarizer, characterized in that: Includes steps: Dissolving the amino-functionalized liquid crystal dye according to claim 1 in acrylic acid, then adding a photoinitiator and a crosslinking agent, and mixing to prepare a liquid crystal coating; The liquid crystal coating is coated on a substrate by a shear coating method, and then ultraviolet irradiation is performed to obtain a coated polarizer.

3. The method for preparing a coated polarizer according to claim 2, characterized in that: The cross-linking agent is one or more of EO-TMPTA, EO-TMTA and PETA.

4. The method for preparing a coated polarizer according to claim 2, characterized in that: The photoinitiator is TPO or photoinitiator-184.

5. The method for preparing a coated polarizer according to claim 2, characterized in that: In the step of dissolving the amino-functionalized liquid crystal dye in acrylic acid, the mass ratio of the liquid crystal dye to the acrylic acid is 1:2-3.

6. The method for preparing a coated polarizer according to claim 2, characterized in that: The usage ratio of the photoinitiator to acrylic acid is 1-2:

100.

7. The method for preparing a coated polarizer according to claim 2, characterized in that: The usage ratio of the crosslinking agent to acrylic acid is 2-10:

10.

8. The method for preparing a coated polarizer according to claim 2, characterized in that: The substrate is a glass substrate or a plastic substrate.

9. A coated polarizer, characterized in that: The coated polarizer is prepared by the preparation method of any one of claims 1 to 8.